Urban [infra]structure : using neglected infrastructure as a framework for the regeneration of inner city voids - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2016)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2016.